Proceedings of the 6th International Conference on Community Development (ICCD 2019) 2019
DOI: 10.2991/iccd-19.2019.152
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Religiosity and Psychological Wellbeing on Organizational Citizenship Behavior

Abstract: This paper describes the effect of religiosity and psychological wellbeing on organizational citizenship behavior. The research hypothesis is that religiosity and psychological wellbeing have a partial or simultaneous effect on organizational citizenship behavior (OCB). The populations are 34 teachers of senior high vocational school. Data was collected through 3 scales, namely the Religiosity Scale, the Psychological Well-being Scale, and the Organizational Citizenship Behavior Scale. The framework that was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…This finding is in congruence with Avey et al (2010) and therefore confirms the reliability of past studies. Further, the results reveal a significant association between psychological well-being and organizational citizenship behaviors, in line with the study of Wibowo (2019). Finally, the results show that the relationship between psychological capital and organizational citizenship behaviors is affected by employee psychological well-being.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is in congruence with Avey et al (2010) and therefore confirms the reliability of past studies. Further, the results reveal a significant association between psychological well-being and organizational citizenship behaviors, in line with the study of Wibowo (2019). Finally, the results show that the relationship between psychological capital and organizational citizenship behaviors is affected by employee psychological well-being.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, happy employees are more likely to go the extra mile for their organization and achieve organizational strategic goals. Wibowo's (2019) study has also suggested a positive influence of psychological well-being on employee organizational citizenship behaviors.…”
Section: Relationship Between Psychological Well-being and Ocbmentioning
confidence: 91%
“…PWB is perceived by civil servants in government organizations directly and significantly increases OCB. This finding supports Wibowo's (2019) research, which found that PWB has a significant effect on OCB.…”
Section: Resultssupporting
confidence: 91%
“…18, no. 1, January 2013 concerning: Study of the Role of Islamic Self-Regulation and Job Characteristics on Organizational Commitment in Employees of Sharia Organizations [18] and the proceedings of the 2nd International Multidisciplinary Conference [3], shows that there is a of job characteristics on organizational commitment [10].…”
Section: The Influence Of Perception Of Job Characteristics On Organi...mentioning
confidence: 99%